SURGICAL REMOVAL OF DENSE POSTERIOR CAPSULE OPACIFICATION AND VITREOUS FLOATERS IN ADULTS BY POSTERIOR CONTINUOUS CURVILINEAR CAPSULORHEXIS THROUGH THE PARS PLANA AND 23-GAUGE VITRECTOMY. Issue 11 (November 2016) - Lin, Jijian; Su, Zhitao; Huang, Xiaodan; Ji, Xian; Yao, Ke
Abstract : Purpose: To evaluate the safety and efficacy of posterior continuous curvilinear capsulorhexis through the pars plana and 23-gauge vitrectomy in surgical management of dense posterior capsule opacification and vitreous floaters. Methods: Fifteen pseudophakic eyes of 15 patients with dense posterior capsule opacification and vitreous floaters between September 2012 and June 2014 were included; after vitrectomy, posterior continuous curvilinear capsulorhexis through the pars plana was performed. Data were collected, including baseline preoperative characteristics, postoperative outcomes, complications, and a modified quality-of-life survey that patients completed. Results: No intraoperative or postoperative complications were encountered in any of the 15 cases. Mean Snellen best-corrected visual acuity was 20/250 preoperatively and improved to 20/32 postoperatively ( P < 0.001). All patients showed normal intraocular pressure 7 days after the procedure. The mean overall corneal endothelial cell loss at postoperative Month 3 was 1.2%. Approximately 80% of the patients had no complaint of vitreous floaters after the procedure. Except for 1 patient (7%) diagnosed with age-related macular degeneration, the rest of the patients (93%) were satisfied with the procedure and would recommend it to friends with dense posterior capsule opacification and vitreous floaters. Conclusion: Posterior continuous curvilinear capsulorhexis through the pars plana combined with 23-gauge vitrectomy may be used to remove dense posterior capsule opacification and vitreous floaters in pseudophakic eyes. Abstract : This study was based on 15 pseudophakic eyes with dense posterior capsule opacification and vitreous floaters; after vitrectomy, posterior continuous curvilinear capsulorhexis through the pars plana was performed. Ninety-three percent of patients showed improved visual acuity, symptoms, and quality of life. Posterior continuous curvilinear capsulorhexis through the pars plana combined with vitrectomy may be an alternative for dense posterior capsule opacification with floaters.